An evaluation of policies and procedures of successful pharmaceutical exporters and the comparison of Iranian counterpart policy - Meysam Seyedifar; Shokufeh Nikfar; Akbar Abdollahi-Asl; HamidReza Rasekh; Ashkan Ehsani; Abbas Kebriaeezadeh (Tehran University of Medical Sciences, 2015)
Background: The volume of the global pharmaceutical market reached 956 billion US dollars in 2011. The reported volume of global exported pharmaceutical products in 2010 exceeds $585 billion. Despite the potential of the market and the suitable geographical location, the volume of Iran's pharmaceutical export has been reported to be only 122 million dollars in the year 2011. Experimental: The purpose of current cross-sectional study was to evaluate the pharmaceutical industries' situation and identify effective factors in pharmaceutical products exportation in successful exporting countries and to compare the results with the situation of pharmaceutical industries in Iran and the factors affecting their exportation experiences. Therefore, we devised an analytic open-ended questionnaire consisting 32 questions in 8 fields. The subjects were 20 experts of pharmaceutical industries, pharmaceutical products exporting companies, and relevant governmental sections. Relevant information on pharmaceutical industries and exportation of pharmaceutical products by target countries was collected through library and the Internet research. Results: All the studied countries had experienced growth in pharmaceutical export during recent years, the fastest growth was in China with 24.8% in 2010. These countries' volume of pharmaceutical export varied from Spain with more than $11 billion in 2011, to Egypt with $250 million in 2010. The worth of Iran's pharmaceutical export was only $122 million in 2011 which was unfavorable. Interviewees' ideas about Iran's situation in pharmaceutical export were obtained through the questionnaire. Accordingly, the emphasized factors impeding improvement of pharmaceutical export in Iran were: lack of motivation as a result of not feeling the need to change, weakness in representing quality of products by producing documentaries and obtaining international standards, shortages in the industry structure and facilities, inadequate progression in new technologies, lack of a competitive view in pharmaceutical industries, the poor share for research and development (R&D) in these companies, discordant and unstable policies and laws regarding exportation, short period of positions held by managers, lack of a vision towards exportation, shortage of experts in marketing and exportation of pharmaceutics, lack of supportive policy-making by the government to help exportation through providing transportation facilities, insurance issues, not rewarding successful exporters, not establishing regional and international relationships, lack of prioritizing economical relationships with other countries through political negotiations, shortage in introducing Iranian pharmaceutical products to allied countries with harmonious policies, not building favorable infrastructures in the fields of information and equipment, no substantial long-term planning with an export-oriented view, no support for modernization of pharmaceutical industries, no encouraging funding in R&D section through tax breaks, inadequate provision of facilities to hold congresses, etc. Conclusion: While Iran has not experienced a successful exporting process, India, Jordan, Spain and China have taken successful steps in the field of exportation during recent years by implementing desirable exports expanding policies. It seems that disharmonies and lack of desirable policy and insufficiencies of applied procedures are responsible for mentioned situation of Iran.